Analysis of postoperative reintervention for thoracoabdominal aortic aneurysm treated with fenestrated/branched endovascular repair - Pan, Zhaohui; Fu, Dongsheng; Hu, Jianhang; Han, Yuexue; Liu, Zhao (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveFenestrated/branched endovascular repair (F/B EVAR) has emerged as a frontline treatment for complex aortic diseases, yet multiple studies have reported high reintervention rates postoperatively. This study aims to discuss strategies for improving patient prognosis by analyzing the reintervention status following F/B EVAR in a single-center patient cohort.MethodsThis is a single-center retrospective study that collected clinical data and follow-up information from patients who underwent F/B EVAR for complex thoracoabdominal aortic aneurysms between January 2018 and June 2024. The study investigated risk factors leading to reintervention, the association between reintervention and postoperative complications and mortality, and other related aspects.ResultsA total of 103 patients were included, with 21 patients undergoing a total of 35 reinterventions during the follow-up period. Among these, 19 reintervention events occurred within 12 months after F/B EVAR (19/103, 18.4%). The reintervention group had significantly higher rates of hypertension, prior endovascular surgery, larger maximum aneurysm diameters, longer operative durations, and more postoperative ICU days compared to the non-reintervention group (P < 0.05). Hypertension (OR: 10.239, 95% CI: 0.999–104.916), maximum aneurysm diameter (OR: 1.591, 95% CI: 1.035–2.446), and operative duration (OR: 1.010, 95% CI: 1.004–1.017) were independent risk factors for reintervention. The most common reintervention methods were SMA branch stent implantation (4/35, 11.4%) and embolization of aortic endoleaks (4/35, 11.4%). The primary indication for reintervention was type IIIc endoleak (12/35, 34.3%). Most patients undergoing reintervention were discharged after interventional or open treatment, with 2 deaths post-intervention (2/21, 9.5%), a higher mortality rate than the non-reintervention group (3/82, 3.7%), but the difference was not statistically significant (P = 0.269).ConclusionHypertension, maximum aneurysm diameter, and operative duration were independent risk factors for reintervention. Type IIIc endoleak was the primary indication for unplanned postoperative reintervention, and interventional treatment was the most common reintervention method. Early postoperative follow-up is crucial, and personalized follow-up strategies and surgical approach selection are key to improving long-term prognosis.